Pemanfaatan Sumber Karbohidrat yang berbeda (umbi suweg dan umbi kimpul) sebagai Subtitusi Media PDA (Potato Dextrose Agar) untuk Pertumbuhan Jamur - Faradiana, Rahma (2016)
Fungus needs some nutrients especially carbohydrate for its growth. Media commonly used for the growth of fungus is PDA (Potato Dextrose Agar). In other side many carbohydrate source like suweg and kimpul tubers is not to be used. This study aims to determine the carbohydrate source from suweg and kimpul tubers are commonly used for PDA substitution media in the growth of fungus. This research was an experimental study using a completely randomized design (CRD) two factors, one was the type of fungus Candida albicans (J1 ) and Aspergillus niger (J2). Second factor was the type of media PDA (M0), suweg tuber media (M1), kimpul tuber media (M2). In this research, Candida albicans used spread plate method for 2 days with a temperature of 280 C and Aspergillus niger used agar block method for 3 days with a temperature of 280 C. Parameter of research was the number of the population Candida albicans , colony diameter and sporulation of Aspergillus niger. Data were analyzed with qualitative quantitative methods. The result of this research showed that the best growth of Candida albicans in PDA media with a population of 1.8 x 109 CFU / ml, the best growth for Aspergillus niger was after 72 hours in PDA media with a colony diameter of 48.3 mm, the best sporulation was PDA media. The best sequence of growth of Candida albicans and Aspergillus niger was PDA media, "kimpul" tuber media, and "suweg" tuber media. So, it can be concluded that the suweg and kimpul tubers can be used as a substitution media of PDA for growth of Candida albicans and Aspergillus niger.